Waitstaff Service Quality and Guest Satisfaction at Mentawai Restaurant, Pangeran Beach Hotel Padang - Rizki Rahmat Wahyudi; Lise Asnur (Pt. Threeple Herphi Educate, 2026)
This study examines the relationship between waitstaff service quality and guest satisfaction at Mentawai Restaurant, Pangeran Beach Hotel Padang. A quantitative cross-sectional survey was conducted with 370 guests selected through purposive sampling from a population record of 29,337 guest visits during September 2022 to March 2023. Eligible respondents were guests who had experienced dining service at Mentawai Restaurant and were able to evaluate direct interaction with the waitstaff. Data were collected using a five-point Likert-scale questionnaire and analyzed in SPSS 26 using descriptive statistics, assumption testing, and simple linear regression. Waitstaff service quality achieved 65.75% of the ideal score and guest satisfaction reached 62.72%, both classified as sufficient under the study's scoring convention. Responsiveness was the lowest service-quality dimension (64.28%), while revisit intention was the lowest satisfaction indicator (62.27%). The residuals met the reported normality criterion (p = 0.200), the archived homogeneity test was non-significant (p = 0.211), and deviation from linearity was non-significant (p = 0.641). Service quality was positively associated with guest satisfaction (B = 0.453, beta = 0.827, t = 28.256, p < 0.001), and the model explained 68.4% of the observed variance. The results indicate that management should prioritize response speed, order accuracy, menu knowledge, complaint handling, and individualized attention while maintaining professional appearance.